Risk and promise: an 11-year, single-center retrospective study of severe acute GVHD in pediatric patients undergoing allogeneic HSCT for nonmalignant diseases - Zaidman, Irina; Even-Or, Ehud; Aharoni, Elroee; Averbuch, Dina; Dinur-Schejter, Yael; NaserEddin, Adeeb; Slae, Mordechai; Shadur, Bella; Stepensky, Polina (Frontiers in Pediatrics, 2023)
Background: Hematopoietic Stem Cell Transplantation (HSCT) is the only curative option for many non-malignant hematopoietic-derived diseases in pediatric patients. Survival after HSCT has improved in recent years and resulted in a 90% survival rate and cure in some non-malignant diseases. Graft-versus-host disease (GVHD) remains a frequent and major complication of HSCT, and a leading cause of morbidity and mortality. Prognosis of patients with high grade GVHD is dismal, with survival rates varying from 25% in the adult population to 55% in pediatric patients. Methods: The main aim of this study is to evaluate the incidence, risk factors and outcome of severe acute GVHD (AGVHD) in pediatric patients with non-malignant diseases, following allogeneic HSCT. Clinical and transplant data was retrospectively collected for all pediatric patients who underwent allogeneic HSCT for non-malignant diseases at Hadassah Medical Center between 2008 and 2019. Patients who developed severe AGVHD were compared with those who did not. Results: A total of 247 children with nonmalignant diseases underwent 266 Allogeneic HSCT at Hadassah University Hospital over an 11 year period. 72 patients (29.1%) developed AGVHD, 35 of them (14.1%) severe AGVHD (grade 3-4). Significant risk factors for developing severe AGVHD were unrelated donor (UD) (p<0.001), mismatch donor (p<0.001) and use of peripheral blood stem cells (PBSC) (p<0.001). Survival rates of pediatric patients with severe AGVHD was 71.4%, compared with 91.9% among those with mild (grade 1-2) AGVHD and 83.4% among patients without AGVHD (p=0.067). Conclusions: These results demonstrate a high survival rate in pediatric patients with non-malignant diseases despite severe GVHD. Significant mortality risk factors found in these patients were the source of donor PBSC (p=0.016) and poor response to steroid treatment (p=0.007).